1993
DOI: 10.1017/s0016672300031220
|View full text |Cite
|
Sign up to set email alerts
|

Spontaneous mutation for a quantitative trait inDrosophila melanogaster. II. Distribution of mutant effects on the trait and fitness

Abstract: SummaryStarting from a completely homozygous population of Drosophila melanogaster, lines have been derived and subjected to 47 generations of divergent selection for abdominal bristle number (20 lines selected in each direction) or to 60–67 generations of inbreeding (100 B lines maintained by a single brother-sister mating, 100 C lines maintained by two double first cousin ma tings). In the selected lines, 25 were identified carrying at least 30 mutations affecting bristle number. A large fraction of these mu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

8
41
0

Year Published

1996
1996
2009
2009

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 64 publications
(49 citation statements)
references
References 21 publications
8
41
0
Order By: Relevance
“…David et al (1993) showed that, in a finite population under selection, the (Mukai et al, 1972;Lopez and Lopez-Fanjul, 1993;Keightley, 1996). Such empirical data combined with theoretical considerations (Charlesworth et al, 1993) [Muller, 1964!…”
Section: Introductionmentioning
confidence: 99%
“…David et al (1993) showed that, in a finite population under selection, the (Mukai et al, 1972;Lopez and Lopez-Fanjul, 1993;Keightley, 1996). Such empirical data combined with theoretical considerations (Charlesworth et al, 1993) [Muller, 1964!…”
Section: Introductionmentioning
confidence: 99%
“…This incorporates the empirical observation that the distribution of genetic effects well as genotypes and include all markers as random variables in a single model. The ability to incorporate is heavy tailed (Lopez and Lopez-Fanjul 1993;Keightley 1994;Keightley and Ohnishi 1998). These paravailable information into QTL mapping and update with newly observed data is an advantage provided tially informative prior distributions not only shrink the estimates of the QTL effects toward zero to avoid the uniquely by Bayesian analysis.…”
mentioning
confidence: 99%
“…Our choice to limit the number of lines studied allowed us to employ a crossing design and degree of replication that together provided sufficient power to detect effects that are relatively small (e.g., ,2% for earlier bolting and 3.5% for enhanced fruit production), although of an evolutionarily considerable magnitude. Moreover, only 4 of the 8 lines were chosen at random; the remaining 4 evaluated in set A were chosen on the basis of suggestive (not statistically significant) evidence that they might be extreme with respect to one or more morphological traits, a common practice in studies of this kind (e.g., Lopez and Lopez-Fanjul 1993;Peters et al 2003). Both because the number of lines is small and because some were included on the basis of preliminary findings, our study, like others of this kind, cannot yield generalizations about the dominance of single mutations.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, lines 17-69 and 17-76 produced fewer leaves, and those of 17-76 were smaller than those of other lines (R. G. Shaw and D. L. Byers, unpublished results). Studies of gene action of mutations have typically focused on effects in lines chosen according to phenotype (e.g., Lopez and Lopez-Fanjul 1993;Peters et al 2003). The second crossing block (set B) involved lines sampled at generation 24 of line advancement, including 24-3, 24-23, 24-39, and 24-102 and lines 0-7 and 0-18.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation